Introduction to Metal Fatigue: Concepts and Engineering Approaches - Pedersen, Mikkel Melters (Technical Report Mechanical Engineering, 2018)
This report contains a compendium written for a fatigue course at Aarhus University during 2016-2018. It introduces the basic concepts governing fatigue strength of metals and presents associated engineering approaches needed for practical application. Both machined components and welded (steel) structures are covered and similarities and differences are discussed.